Mineralogy as a potential driver of irregular radiocarbon patterns among Icelandic fluvial carbon pools - Nora Gallarotti; Lisa Bröder; Julie Lattaud; Stephan Wartenweiler; Negar Haghipour; Timothy I Eglinton (Environmental Research Letters)
Fluvial export of organic carbon (OC) from the terrestrial biosphere to the ocean forms a key component of the global carbon cycle. Carbon sources and transformations along the land–ocean aquatic continuum are dynamic with a complex interplay between particulate and dissolved organic and inorganic carbon pools (POC, DOC, DIC). Radiocarbon dating serves as a valuable tool, providing crucial insights into turnover and residence times within these pools. However, the myriad of carbon sources, including ancient ‘petrogenic’ OC from sedimentary rocks or freshly assimilated OC derived from aquatic in-situ production, makes it challenging to interpret ^14 C signatures in the context of terrestrial biospheric OC turnover and residence times. Icelandic rivers and streams offer an opportunity to examine biospheric carbon dynamics due to the virtual absence of petrogenic OC (e.g., shales, carbonates) in underlying bedrock. Our study of 43 rivers and streams, collectively draining approximately 42% of Iceland’s surface, revealed that radiocarbon signatures of POC largely align with global river patterns but lacked the presence of significantly old ( ^14 C-depleted) carbon likely reflecting the absence of ancient petrogenic OC. In contrast, DOC tended to be older compared to global rivers and the corresponding POC and DIC pools in Icelandic rivers. These observations challenge the paradigm that riverine POC generally exhibits longer turnover and residence times than DOC. After excluding other potential factors, we argue that this apparent age inversion among carbon pools in Icelandic rivers may reflect retention of DOC prior to its release to the aquatic continuum through interactions with high surface area minerals prevalent in the volcanic soils of Iceland. This finding may be relevant for other fluvial systems draining volcanic bedrock and have broader implications regarding biospheric OC dynamics in rivers and streams globally.